Changement climatique et développement des territoires de montagne : quelles connaissances pour quelles pistes d’action ? - Didier Richard; Emmanuelle George-Marcelpoil; Vincent Boudières (Revue de Géographie Alpine)
Climate change is today a reality at both the international and more local levels. Recent studies have focussed mainly on analysing the consequences of climate change. The present article seeks to examine and qualify the impact of climate change in the mountain areas of the Alps. A first line of enquiry concerns the changing level of danger in the mountain environment. Are mountain areas becoming more dangerous and, if so, in terms of what types of risks and to what degree? However, adopting an approach based on an analysis of natural hazards and their dynamics in response to climate change cannot ignore the economic activities and types of development that already exist in these areas. In this respect, the tourism economy is predominant in mountain regions. Its durability and vitality undoubtedly constitute a priority for local actors. It is not surprising therefore that the latter have set up strategies for adapting to climate change. For planners and decision-makers to ensure integrated approaches in dealing with climate change, it is important that the complex links between natural risks and the types of development in mountain areas are better understood, which calls for a more detailed analysis of the environment in terms of territorial vulnerability.